KEEFEKTIFAN MODEL QUANTUM TEACHING TERHADAP HASIL BELAJAR TEMA INDAHNYA KEBERSAMAAN SISWA KELAS IV SD NEGERI 03 KALIRANDU PETARUKAN PEMALANG - Septi Suharyati, Riris Setyo Sundari, (MALIH PEDDAS, 2015)
Top of FormLearning is less varied and innovative will make students feel bored, so the reduced student participation in the learning process, especially on the theme of beauty of togetherness. A teacher should change in the hope of learning strategies make students more interested, by using a model of effective and meaningful learning. One alternative that is given by applying the model of Quantum Teaching the Beauty of Mutual learning theme. The problems revealed in this study is whether the model of Quantum Teaching effectively to improve learning outcomes Beautiful theme Unity Elementary School fourth grade students 03 Kalirandu Petarukan Pemalang? Goals to be achieved in this study was to determine whether the model Quatum Teaching effectively to improve learning outcomes Beautiful theme Unity Elementary School fourth grade students 03 Kalirandu Petarukan Pemalang. This research is a quantitative experiment. The population in this study were all fourth grade students of SD Negeri 03 kalirandu Petarukan Pemalang. The sample used in this study were class IV, which has 21 students using Saturated sampling. The data in this study was obtained through a test instrument with multiple choice answers and observations during the lesson. Design research is an experimental design with pre-test type of Pre and Post-test Design Group. Based on the analysis of experimental data showed that after receiving treatment using a learning model of Quantum Teahing eferktif on learning outcomes Indahya Mutual theme initially has an average value of 58.8571 then the average value becomes 81.9047. This is evidenced by the analysis of the final results of the pre-test and post-test with the t test t count> t table is 13.93> 2:09 so there is a significant difference or Ho rejected. That coupled with the increased involvement of the student.